The One-dimensional Fuzzy Ising Model - Souza, Renatto Barbosa de (Physicae Organum, 2018)
This work uses Fuzzy Sets Theory to develop analytical tools in order to guide the construction of the fuzzy phase diagram associated to the one-dimensional spin-1/2 Ising model subject to an external magnetic field, taking into account uncertainties presents in both exchange parameter J and magnetic field h. After that, by utilizing the fuzzy phase diagram just constructed, the consequences arising from those uncertain parameters on graphs of a few thermodynamics quantities such as magnetization and entropy are analyzed.